Towards a deeper understanding of impression formation: new insights gained from a cognitive-ecological perspective - Ziegler, Johannes; Krueger, Joachim I.; Fiedler, Klaus (Journal of personality and social psychology, 2018)
Impression formation is a basic module of fundamental research in social cognition, with broad implications for applied research on interpersonal relations, social attitudes, employee selection, and person judgments in legal and political context. Drawing on a pool of 28 predominantly positive traits used in Solomon Asch’s (1946) seminal impression studies, two research teams have investigated the impact of the number of person traits sampled randomly from the pool on the evaluative impression of the target person. Whereas Norton, Frost, and Ariely (2007) found a “less-is-more” effect, reflecting less positive impressions with increasing sample size n, Ullrich, Krueger, Brod, and Groschupf (2013) concluded that an n-independent averaging rule can account for the data patterns obtained in both labs. We address this issue by disentangling different influences of n on resulting impressions, namely varying baserates of positive and negative traits, different sampling procedures, and trait diagnosticity. Depending on specific task conditions, which can be derived on theoretical grounds, the strength of resulting impressions (in the direction of the more prevalent valence) (a) increases with increasing n for diagnostic traits, (b) is independent of n for nondiagnostic traits, or (c) decreases with n when self-truncated sampling produces a distinct primacy effect. This refined pattern, which holds for the great majority of individual participants, illustrates the importance of strong theorizing in cumulative science (Fiedler, 2017) built on established empirical laws and logically sound theorizing. (PsycINFO Database Record (c) 2018 APA, all rights reserved)